Navigating Challenges: Educators' Perspectives on Teaching English to Inclusive Students in Regular Classrooms - Meirlyn Bunga Ambar; Fahmy Imaniar; Ita Eka Oktaviani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to explore how English teachers address the challenges of teaching in regular classrooms that include students with special educational needs. Employing a qualitative case study design, the research gathered data through semi-structured interviews and classroom observations in inclusive junior high school classes at SMPN 35 Surabaya. This approach allowed for an in-depth understanding of teachers’ experiences in balancing the learning needs of both regular and inclusive students. The findings reveal that teachers encounter several obstacles, including limited time, lack of specialized training, insufficient teaching resources, and rigid curriculum demands. Despite these challenges, teachers apply a range of differentiated instructional strategies such as simplifying materials, using visual and auditory media, implementing peer tutoring, and designing tailored worksheets. These strategies help inclusive students remain engaged while motivating regular students to participate actively. The study highlights the need for ongoing professional development, flexible school policies, and adequate facilities to strengthen inclusive practices. The results contribute practical insights for policymakers and teacher education programs by underscoring the importance of equipping teachers with concrete strategies such as peer collaboration, differentiated materials, and adaptive assessments to improve inclusive English language teaching.